Kekuatan Hukum Terhadap Pejabat Tata Usaha Negara Yang Tidak Menjalankan Putusan Pengadilan Tata Usaha Negara - Hayoto, Muhammad Rifandi; Alfons, Saartje Sarah; Pattipawae, Dezonda Rosiana (Jurnal Saniri, 2022)
Introduction: The 1945 Constitution of the Republic of Indonesia (hereinafter abbreviated to the 1945 Constitution of the Republic of Indonesia), Article 24 paragraph (1) states that "Judicial power is an independent power to administer justice to uphold law and justice" and paragraph (2) states that " Judicial power is exercised by a Supreme Court and judicial bodies under it in the general court environment, the religious court environment, the military court environment, the state administrative court environment, and by a Constitutional Court.Purposes of the Research: To find out and analyze the legal force of State Administrative Officials who do not carry out the Decisions of the State Administrative Court.Methods of the Research: This research is a normative legal research with analytical descriptive nature. This research is intended to obtain normative clarity by identifying and analyzing the application of sanctions against State Administrative Officials who do not implement the Decisions of the State Administrative Court with permanent legal force.Results / Findings / Novelty of the Research: The results of this study indicate that the weak implementation of State Administrative Court Decisions is due to the absence of an executorial institution and coercive power in implementing State Administrative Court Decisions, so that the implementation of State Administrative Court Decisions depends on the awareness and initiative of State Administrative Officials.